Essentials of marketing research putting research into practice - Clow, Kenneth E.; James, Karen E. (Thousand Oaks, Calif. ; London : SAGE, 2013)
This text offers a hands-on, applied approach to developing the fundamental data analysis skills necessary for making better management decisions using marketing research results. Clow and James explore the latest research techniques, including social media and other online methodologies, and they examine current statistical methods of analyzing data.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Marketing research